SELECTION OF OBTURATION MATERIALS IN PULPECTOMY TREATMENT OF DECIDUOUS TEETH: Pemilihan Bahan Obturasi Pada Perawatan Pulpektomi Gigi Desidui - Laksmita Tanjung; Bambang Tri Hartomo; Mahindra Awwaludin Romdlon; Fitri Diah Oktadewi (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2021)
Introduction: Pulpectomy is the procedure of taking the entire pulp tissue from all the roots and corona of a tooth. There are several materials for obturation / root canal fillers in deciduous teeth, namely zinc oxide eugenol (ZOE), calcium hydroxide and iodoform paste a mixture of calcium hydroxide. A 6 year old boy patient came to RSGM with his parents seeking for treatment a tooth with a large cavity in the upper left posterior region and had been pain before. Intraoral examination revealed deep caries in the occlusal tooth 65 which reaching the pulp, percussion (-), palpation (-), mobility (-), vitality (-). Radiographic examination of tooth 65 showed a radiolucent image that had reached the pulp and the root canals had not yet undergone resorption. The diagnosis of this case was pulp necrosis at tooth 65. Case management: The treatment plan to be carried out was non-vital pulpectomy on tooth 65 and used technique non-vital pulpectomy because the tooth had already necrosis. Discussion: The filler used is ZOE. The reason for choosing this material was because it was indications for the use of ZOE material for teeth with necrosis. Conclussion: ZOE has anti-inflammatory and analgesic properties that can reduce pain.